Fatores Político-Econômicos do Desmatamento na Amazônia Oriental - Gazoni, Jefferson Lorencini; Mota, José Aroudo (Sustainability in Debate, 2010)
This paper studies the relationships between political and productive activities and the deforestation in Eastern Amazon biome with the purpose of evaluating the main factors of the latest regional forest’s deforestation. Methodologically, it used a multiple regression of the districts in Eastern Amazon from 2007 to 2008. The results evidenced that the primary driving forces of the recent deforestation in region are the bovine cattle breeding and agriculture, the wooden and charcoal production, the extraction of non timber forest products, the distance for National Environmental Offices in region, the protected areas and the forest stock. In this context, the researches on deforestation have to focuses on the economic activities that can protect de forest against deforestation.